Caspase-1 activation, IL-1/IL-6 signature and IFNγ-induced chemokines in lungs of COVID-19 patients - Cambon, Audrey; Guervilly, Christophe; Delteil, Clémence; Potere, Nicola; Bachelier, Richard; Tellier, Edwige; Abdili, Evelyne; Leprince, Marine; Giani, Marco; Polidoro, Ildo; Albanese, Valentina; Ferrante, Paolo; et al. (Frontiers in Immunology, 2025)
RationaleCOVID-19-associated acute-respiratory distress syndrome (C-ARDS) results from a direct viral injury associated with host excessive innate immune response mainly affecting the lungs. However, cytokine profile in the lung compartment of C-ARDS patients has not been widely studied, nor compared to non-COVID related ARDS (NC-ARDS).ObjectivesTo evaluate caspase-1 activation, IL-1 signature, and other inflammatory cytokine pathways associated with tissue damage using post-mortem lung tissues, bronchoalveolar lavage fluids (BALF), and serum across the spectrum of COVID-19 severity.MethodsHistological features were described and activated-caspase-1 labeling was performed in 40 post-mortem biopsies. Inflammatory cytokines were quantified in BALF and serum from 19 steroid-treated-C-ARDSand compared to 19 NC-ARDS. Cytokine concentrations were also measured in serum from 128 COVID-19 patients at different severity stages.Measurements and main resultsTypical “diffuse alveolar damage” in lung biopsies were associated with activated caspase-1 expression and vascular lesions. Soluble Caspase-1p20, IL-1β, IL-1Ra, IL-6 and at lower level IFNγ and CXCL-10, were highly elevated in BALF from steroid-treated-C-ARDS as well as in NC-ARDS. IL-1β appeared concentrated in BALF, whereas circulating IL-6 and IL-1Ra concentrations were comparable to those in BALF and correlated with severity. TNFα, TNFR1 and CXCL8 however, were significantly higher in NC-ARDS compared to C-ARDS, treated by steroid.ConclusionsIn the lungs of C-ARDS, both caspase-1 activation with a predominant IL-1β/IL-6 signature and IFNγ -associated chemokines are elevated despite steroid treatment. These pathways may be specifically targeted in ARDS to improve response to treatment and to limit alveolar and vascular lung damage.